The salted radish takuan-zuke shows antihypertension effects in spontaneously hypertensive rats. Issue 10 (29th September 2017) - Kumakura, Kei; Kato, Ryo; Kobayashi, Taito; Kimura, Norihisa; Takahashi, Hitoe; Takahashi, Asaka; Matsuoka, Hiroki
Abstract : Recently, we reported that the antihypertensive compound, γ-aminobutyrate (GABA), increases over time during the dehydration of salted radish, known as takuan-zuke, a popular pickle in Japan. Abstract : Recently, we reported that the antihypertensive compound, γ-aminobutyrate (GABA), increases over time during the dehydration of salted radish, known as takuan-zuke, a popular pickle in Japan. The objective of this study was to clarify the antihypertensive effects of takuan-zuke . We prepared two types of takuan-zuke by sun-drying ( hoshi takuan-zuke ) and salt-pressing ( shio-oshi takuan-zuke ) using dehydration processes. The oral administration of takuan-zuke lowered systolic blood pressure in spontaneously hypertensive rats (SHRs). Shio-oshi takuan-zuke (SR) demonstrated a clear antihypertension effect compared with hoshi takuan-zuke (DR), despite equal GABA concentrations in the feed. Furthermore, takuan-zuke demonstrated angiotensin converting enzyme (ACE) inhibition in vitro . These findings indicated that takuan-zuke contains unknown substances that have hypotensive actions independent of GABA. Further evaluation revealed that takuan-zuke contains polyphenols, arginine, and α-linolenic acid as possible antihypertensive factors. Collectively, our results suggest that the salty Japanese food takuan-zuke has antihypertensive effects in vivo, likely involving complex mechanisms.